EZH2: Its regulation and roles in immune disturbance of SLE - Yang, Yiying; Liu, Ke; Liu, Meidong; Zhang, Huali; Guo, Muyao (Frontiers in Pharmacology, 2022)
The pathogenesis of systemic lupus erythematosus (SLE) is related to imbalance of immune homeostasis. Epigenetic mechanisms have played significant roles in the breaking of immune tolerance. Enhancer of zeste homolog 2 (EZH2), the specific methylation transferase of lysine at position 27 of histone 3, is currently found to participate in the pathogenesis of SLE through affecting multiple components of immune system. Therefore, this review mainly expounds the mechanisms underlying EZH2-mediated break of immune homeostasis in patients with SLE, hoping to provide new ideas in the pathogenesis of SLE and new targets for future treatment.